5(6x+35)+7(x+1)=u

Simple and best practice solution for 5(6x+35)+7(x+1)=u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(6x+35)+7(x+1)=u equation:


Simplifying
5(6x + 35) + 7(x + 1) = u

Reorder the terms:
5(35 + 6x) + 7(x + 1) = u
(35 * 5 + 6x * 5) + 7(x + 1) = u
(175 + 30x) + 7(x + 1) = u

Reorder the terms:
175 + 30x + 7(1 + x) = u
175 + 30x + (1 * 7 + x * 7) = u
175 + 30x + (7 + 7x) = u

Reorder the terms:
175 + 7 + 30x + 7x = u

Combine like terms: 175 + 7 = 182
182 + 30x + 7x = u

Combine like terms: 30x + 7x = 37x
182 + 37x = u

Solving
182 + 37x = u

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-182' to each side of the equation.
182 + -182 + 37x = -182 + u

Combine like terms: 182 + -182 = 0
0 + 37x = -182 + u
37x = -182 + u

Divide each side by '37'.
x = -4.918918919 + 0.02702702703u

Simplifying
x = -4.918918919 + 0.02702702703u

See similar equations:

| -2y+10=-2(2y+3) | | x-4=-13 | | 16x^2+y^2-16y=0 | | r+10=15 | | 16x^2+y^2=16y | | -2+x=26 | | 2.1=x-6.1 | | (12)(6)6=x | | 3p=18 | | -10x=70 | | -7x=-168 | | -10.1x=30.3 | | 100(84)=96x | | -10x-20=-190 | | 4x+10x=56 | | 12z=-8 | | -11=x+4 | | 3x^2y+6x^2y^2-144xy^3= | | x^2-3x=-8 | | x=4+-3y | | x^2-18+77= | | 4(2x+-1)=27+3(2x-5) | | x(x+3)=18 | | 38=25+2y | | 7p=6p^2-3 | | v^2-6v+15= | | 0=-16t^2+35t+8 | | 1-5x^2=-3x | | 3(q+4)-10q=2q+3 | | 2x+3x+5=5(2x-3) | | 4z-2(z+6)=7z+8 | | 5x^2-30x-80= |

Equations solver categories